2001
DOI: 10.1185/0300799039117037
|View full text |Cite
|
Sign up to set email alerts
|

Oral Montelukast Versus Inhaled Beclomethasone in 6- to 11-year-old Children with Asthma: Results of an Open-label Extension Study Evaluating Long-term Safety, Satisfaction, and Adherence with Therapy

Abstract: This 6-month, open-label extension study of a previously described base study compared oral montelukast with inhaled beclomethasone in terms of safety, forced expiratory volume in one second (FEV1) measurements, parent and patient satisfaction with treatment, asthma-related medical resource utilization, school absenteeism, and parental work loss in children with asthma. A total of 124 of 266 asthmatic children, 6 to 11 years of age, who enrolled in the base study entered a 6-month open-label extension study (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 28 publications
1
7
1
2
Order By: Relevance
“…montelukast experienced similar clinical outcomes, including changes in forced expiratory volume in 1 second and decreases in airway obstruction, asthma symptom scores, and asthma-related health care resource use. 22,23 Although contrary to findings of clinical trials reporting superior efficacy of fluticasone over montelukast under tightly controlled conditions, our results more accurately represent patients' experience in clinical practice. Our results confirmed much of the existing body of observational studies on resource use indicating that significant differences are not seen in patient outcomes with fluticasone or montelukast therapy.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…montelukast experienced similar clinical outcomes, including changes in forced expiratory volume in 1 second and decreases in airway obstruction, asthma symptom scores, and asthma-related health care resource use. 22,23 Although contrary to findings of clinical trials reporting superior efficacy of fluticasone over montelukast under tightly controlled conditions, our results more accurately represent patients' experience in clinical practice. Our results confirmed much of the existing body of observational studies on resource use indicating that significant differences are not seen in patient outcomes with fluticasone or montelukast therapy.…”
Section: Discussioncontrasting
confidence: 94%
“…Open-label extension studies comparing the impact of asthma treatments suggest that longterm asthma outcomes are similar among these treatment groups. 22,23 Results of observational studies involving patients with asthma have shown similar improvements in hospitalizations and emergency department visits among patients prescribed fluticasone and montelukast and have yielded varied results regarding need for rescue drug therapy. [5][6][7][8][9][10]24 The purpose of our study was to reexamine the relative effectiveness of fluticasone and montelukast on asthma-related resource-use patterns based on more recent health care claims data believed to reflect current treatment patterns and outcomes for asthma.…”
mentioning
confidence: 99%
“…Medication adherence is known to decrease as dosing frequency increases (37), and all other therapies in the present analysis have a standard twice-daily dosing regimen. TP was the only oral maintenance therapy assessed in the present analysis, and despite a relatively smaller number of patients, the preference for oral therapy was evident for both adherence and persistence, an effect that has been seen previously in children with asthma (38,39). Therapy with an ICS had the lowest percentage of patients (with either disease) identified as having an adequate level of medication supply (MPR 80-120%), but was also found to have a comparatively high rate of adherence/persistence in the regression analyses.…”
Section: Discussionsupporting
confidence: 59%
“…6 In a 6-month open-label study of 124 children, Maspero et al noted better adherence to montelukast taken once daily than to inhaled beclomethasone prescribed three times per day. 7 Sherman et al 8 used pharmacy refill data to determine adherence to montelukast vs. fluticasone in 161 children. These investigators found subobtimal adherence to both, but patients taking fluticasone were more likely to have very poor adherence, defined as taking less than 50% of their prescribed dose.…”
Section: Introductionmentioning
confidence: 99%